Stunted sexuality in havvthorne's the blithedale romance - Arnold Gordenstein (Ilha do Desterro)
By now a commonplace of Blithedale Romance criticism is that Coverdale is a voyeur. But hardly anyone has related Coverdale's voyeurism to the larger psychological pattern that includes voyeurism and these to its central themes. Otto Fenichel couples voyeurism and toucheurism and defines them as "scoptophilia, the sexualization of the sensations of looking... analogous to touch eroticism." 1 Doubly restricted by Victorian morality as well as by his American Puritan heritage, Hawthorne indicated that the motivations that drew people to and that characterized their relationships at lithedale were, in part, sexual. Since he could not directly describe this sexuality he used sight and touch images to convey the kind of attraction he had in mind.